Evaluating the efficacy of ultrasound-assisted extraction of Plantago major L. leaves by response surface methodology through determination of aucubin levels - Kurnia Rahayu Purnomo Sari; Zullies Ikawati; Retno Danarti; Nur Hasna Nafiisah; Triana Hertiani (Journal of Advanced Pharmaceutical Technology & Research)
Plantago major L. (Plantaginaceae) contains bioactive phytochemicals supporting its wide array of pharmacological activities. Aucubin, a bioactive iridoid glycoside found in P. major, has been used as a marker substance for quality control. This study’s objective was to assess the efficacy of ultrasound-assisted extraction (UAE) on P. major leaf extracts based on the aucubin level. The response surface methodology (RSM) was employed to investigate the impact of process parameters on the UAE. The compound’s studies were developed and validated by the utilization of high-performance liquid chromatography coupled to photodiode array (HPLC-PDA). Four independent variables were studied: extraction temperature (°C), extraction time, ethanol concentration (%), and ratio of solute to solvent. The analytical method used HPLC-PDA to quantify the aucubin content as the dependent variable. The study’s findings indicate that the most favorable conditions for UAE were attained at a temperature of 20°C for 20 min, an ethanol concentration of 25%, and a ratio of 1:5 g/mL. The HPLC-PDA approach that has been verified demonstrates its efficacy as a technique for quantifying the concentration of aucubin in the extract of P. major leaves. The obtained experimental values (5.736% mg/g) for the aucubin content, under the optimal conditions of UAE, exhibited a satisfactory level of concurrence with the values predicted by the RSM (5.774% mg/g). This finding showed that UAE and RSM can be developed as an efficient extraction method for P. major leaves.